2017
DOI: 10.1111/jac.12222
|View full text |Cite
|
Sign up to set email alerts
|

Improving resistance against terminal drought in bread wheat by exogenous application of proline and gamma‐aminobutyric acid

Abstract: Scarcity of water is a severe constraint, which hinders the wheat productivity worldwide. However, foliage application of osmoprotectants may be useful in reducing the drought‐induced yield losses in wheat (Triticum aestivum L.). In this study, potential of foliage applied osmoprotectants (proline, gamma‐aminobutyric acid) in improving the performance of bread wheat against terminal drought was evaluated. Both proline and gamma‐aminobutyric acid (GABA) were foliage applied at 50, 100 and 150 mg/L at anthesis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 36 publications
5
35
0
1
Order By: Relevance
“…In accordance with our findings, Farooq et al (2017) reported that foliage applied GABA at 100 mg/L was more competent than another concentration 150 mg/L in alleviation of drought stress in two cultivars of bread wheat. Also, Krishnan et al (2013) found that GABA supplementation at 50 mM was reported to be more practical than 70 mM in mitigation the damage in perennial ryegrass grown under water deficit condition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with our findings, Farooq et al (2017) reported that foliage applied GABA at 100 mg/L was more competent than another concentration 150 mg/L in alleviation of drought stress in two cultivars of bread wheat. Also, Krishnan et al (2013) found that GABA supplementation at 50 mM was reported to be more practical than 70 mM in mitigation the damage in perennial ryegrass grown under water deficit condition.…”
Section: Discussionsupporting
confidence: 93%
“…The result of our study clearly reported that GABA treatments significantly promoted the endogenous total phenols in garlic (Table 2). In the same context, exogenous GABA promoted the accumulation of phenolic substances in banana fruits, wheat and tomato plants under several types of abiotic stress (Wang et al, 2014;Farooq et al, 2017;Cekiç, 2018). Taken together, positive effect of GABA in increasing the agricultural productivity and mitigation of harmful effect of abiotic stresses probably due to accumulation of total phenols that improves antioxidant defense system, thus improving yield and efficiency of wateruse (Farooq et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Drought or water deficit inhibits plant growth and decreases crop yield. It has been reported that exogenously applied GABA could effectively alleviate drought‐induced decreases in growth and productivity of crops (Farooq et al ; Rezaei‐Chiyaneh et al ). In response to drought and salt stress, transgenic tobacco expressing a GDP‐D‐mannose pyrophosphorylase gene PpGMP maintained better growth performance (Ai et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress can affect the wheat growth at any stage; nonetheless, the terminal drought is most destructive regarding its impact on wheat grain yield (Farooq, Hussain, & Siddique, ; Farooq, Nawaz, Chaudhary, Indrasti, & Rehman, ; Farooq, Nawaz, Chaudhary, & Rehman, ; Nawaz, Farooq, Cheema, Yasmeen, & Wahid, ). Terminal drought stress affects the pollination (Ashraf, ), thus reducing the grain set and eventually the grain yield (Nawaz, Farooq, Cheema, Yasmeen, et al., ).…”
Section: Introductionmentioning
confidence: 99%